Partial Least Square-Structural Equation Modeling as a Model of Community Participation in Macroplastic Waste Management in Cikapundung River (Case Study: Baleendah District) Bandung Regency - Fahriyatun Mufidah, Farah; Kosmaryandi, Nandi; Taryono; Hariyadi, Sigid (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Waste is an environmental issue owing to its increasing amount. The type of waste that is currently an important problem is plastic waste, which can endanger living things and the environment. This study aimed to analyze the community participation factors that affect waste management. This study used interview methods and completed questionnaires from as many as 50 respondents in Baleendah District, West Java Province. The collected data were analyzed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method with the approach of several latent variables, each of which was equipped with indicators. The PLS-SEM model was evaluated using the Outer Model and Inner Models. The results showed that, in the measurement model, all indicators were valid and reliable for measuring the constructed construct. In the structural model of the results of hypothesis testing with the bootstrapping method, it can be concluded that the variables of External Factors and Waste Management significantly affect the variables of Waste Management; the variable of Waste Management significantly affects the variable Impact of Waste Management, while the variable of Waste Reduction insignificantly affects the variable of Waste Management. The results of this study can be used as recommendations for implementing strategies to increase community participation in plastic waste management.